2019
DOI: 10.1136/bmjopen-2018-022670
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect of multiple gestations on the association between in vitro fertilisation and severe maternal morbidities: a retrospective cohort study

Abstract: ObjectiveTo investigate whether the association between in vitro fertilisation (IVF) and severe maternal morbidity (SMM) was mediated by multiple gestations.DesignA retrospective cohort study.SettingThe study was conducted at six hospitals in China.ParticipantsPregnant women at 20 gestational weeks or longer.Outcome measureThe outcome was SMM, which was a composite of potential life-threatening conditions, the use of critical medical interventions, or the status of maternal near-miss that occurred during pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In a retrospective multicentre cohort study by Tan et al 18.7% of women conceived via IVF had multiple pregnancies versus only 1.53% of spontaneous conception (p<0.001). [7][8][9] Increased risk of gestational diabetes mellitus has been observed in many studies done so far similar to that observed in our study. The most probable reason sighted is the high prevalence of polycystic ovarian syndrome in females with infertility.…”
Section: Resultssupporting
confidence: 90%
“…In a retrospective multicentre cohort study by Tan et al 18.7% of women conceived via IVF had multiple pregnancies versus only 1.53% of spontaneous conception (p<0.001). [7][8][9] Increased risk of gestational diabetes mellitus has been observed in many studies done so far similar to that observed in our study. The most probable reason sighted is the high prevalence of polycystic ovarian syndrome in females with infertility.…”
Section: Resultssupporting
confidence: 90%
“…In conception achieved by ART, multiple gestations usually increase the risk of adverse pregnancy outcomes [ 31 , 32 ]. A previous study indicated that GDM following ART was more common in multiple gestations compared to singleton with OR of 1.30 (95% CI 1.10–1.54) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all analyses, we adjusted for maternal demographic factors, pregnancy-related complications and reproductive history that have been suggested to be associated with postpartum bleeding (24)(25)(26)(27). Those covariate variables included maternal age at delivery, parity, gravidity, hypertensive disorders in pregnancy (HDP), GDM, mode of delivery, prolonged second stage of labor, intra-amniotic infection, gestational age at delivery, newborn birthweight, and placental abnormality (placental abruption, placenta previa, low-lying placenta, placenta accrete and increta).…”
Section: Covariate Variablesmentioning
confidence: 99%